An alternative for whom? Rethinking alternative education to break the cycle of educational inequality and inequity - Kim, Jeong-Hee; Taylor, Kay Ann (My University, 2011)
It seems that the growing number of alternative schools correlates to the growing population of disenfranchised students. The more disenfranchised students there are, the more alternative schools are being built. This correlation may be due to social, economic, and political issues that cause pervasive social injustice, which reinforces the cycle of educational inequality. The purpose of this qualitative study is to examine one alternative high school from a critical perspective to determine whether or not the school is beneficial to the students to the extent that it works to break the cycle of educational inequality. Employing critical theory as a theoretical framework, we find that the school is successful in providing a caring environment for the students and gaining trust from the students. However, the school fails to offer a meaningful and equitable alternative education that benefits the students. This failure leads us to question for whom this school is truly an alternative.
Keywords: Alternative education; Cycle of educational inequality; Disenfranchised students